PENGUKURAN BEBAN KERJA ALLOWANCE DAN FULL-TIME EQUIVALENT (FTE) KARYAWAN MIE GACOAN UNTUK MENJAGA PRODUKTIVITAS KARYAWAN - Aditia Fajar D; Iqbal Naufal, Sulthon Muammar S, Paduloh (CV. Adiba Aisha Amira, 2025)
This study aims to analyze employee workload at Mie Gacoan using the Allowance and Full-Time Equivalent (FTE) methods in order to maintain work productivity and efficiency. Data collection was conducted through direct observation on site, involving three main divisions: cashiers, chefs, and waiters. The results showed that the allowance values for cashiers, chefs, and waiters were 34.5%, 35%, and 33%, respectively. FTE calculations revealed that cashiers had a value of 0.93 (underload category), while chefs and waiters had values of 1.09 and 1.16 (normal category), respectively. These findings emphasize the importance of optimizing allowance and FTE values to achieve a balance between operational efficiency, employee job satisfaction, and customer service quality. This optimization is expected to reduce work fatigue, increase productivity, and maintain operational cost efficiency.